Financial Accounting: An Introduction/Managerial Accounting: An Introduction (Book). - Bruns, William J.; Jacobsen, Lyle E. (The Accounting Review, 1968)
Reviews two books by Harold Bierman Jr. and Allian R. Drebin. "Financial Accounting: An Introduction"; "Managerial Accounting: An Introduction."